Characteristics Of Hypospadia Patients In Plastic Reconstructive And Aesthetic Surgery Division At National Hospital Cipto Mangunkusumo Jakarta - Aulia, Indri; Sukasah, Chaula L.; Kusumawardani, Evanti (Jurnal Plastik Rekonstruksi, 2019)
Background : Hypospadias is a genital congenital abnormality with a variable prevalence. There are risk factors associated with hypospadias. This study analyse the characteristics of hypospadias patients, hypospadias with other genital anomalies, and family history of hypospadias. Method : We used the National Hospital Cipto Mangunkusumo Medical Record Database, which contains all the patient's data from 2013 to 2017. All the information of the diagnosis, type of hypospadias, and the family history are provided. After collecting all the data, we analysed the total cases of hypospadias and the characteristic of hypospadias patients. Result : Based on the data, 6,254 patient that registered in the Plastic Surgery Division, forty-nine patients were diagnosed with hypospadias. Among them, 16% are penoscrotal type hypospadias. Furthermore, there is only 3% of the patients who has a history of hypospadias running in the family. Approximately 29.4% of the patients associated with other genital anomalies. However, only 35% of the sample population underwent surgical repair at the age of 0-5 years. Conclusion: The number of hypospadias cases treated by Plastic Surgery Division at The National Hospital Cipto Mangunkusumo is parallel with the global prevalence of hypospadias. The most common hypospadias type treated in Cipto Mangunkusumo Hospital is penoscrotal, which is similar to the previous study in Europe. The prevalence of hypospadias in Indonesia remains unknown therefore, the data management of hypospadias patients ought to be improved.